Analisis KEBIJAKAN PENDANAAN JANGKA PENDEK SEBAGAI MODERASI KINERJA USAHA MENENGAH: KEBIJAKAN PENDANAAN JANGKA PENDEK SEBAGAI MODERASI KINERJA USAHA MENENGAH - SYAMLAN, ADIBA; Syafi'i, Mochamad; Ulum, Bustanul (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
Short-term funding is a type of funding that plays a major role in the operational activities of a business, especially in medium-sized business activities, where it is known that the role of this funding is the backbone of business activities, the business policies implemented in business activities are of concern to researchers, it is clear that this business activity is a popular choice among the surrounding community so that it triggers interest in conducting research at this location, the purpose of this study is to determine the short-term funding policy that is being pursued. The method used is mixed, namely a combination of qualitative and quantitative methods with a total sample of 99 respondents. The results show that the policies carried out by this business activity are centered on strong internal funding, which is considered a policy that is enforced. The conclusion that can be expressed is that this policy is deemed effective and efficient in optimizing business activities, the suggestion is to start directing the role of financial institutions in terms of investment in the securities aspect